[18F]Flortaucipir PET Across Various MAPT Mutations in Presymptomatic and Symptomatic Carriers. (7th September 2021) - Wolters, Emma E.; Papma, Janne M.; Verfaillie, Sander C.J.; Visser, Denise; Weltings, Emma; Groot, Colin; van der Ende, Emma L.; Giannini, Lucia A.A.; Tuncel, Hayel; Timmers, Tessa; Boellaard, Ronald; Yaqub, Maqsood; et al.
Abstract : Objective: To assess the [ 18 F]flortaucipir binding distribution across MAPT mutations in presymptomatic and symptomatic carriers. Methods: We compared regional [ 18 F]flortaucipir binding potential (BPND ) derived from a 130-minute dynamic [ 18 F]flortaucipir PET scan in 9 (pre)symptomatic MAPT mutation carriers (4 with P301L [1 symptomatic], 2 with R406W [1 symptomatic], 1 presymptomatic L315R, 1 presymptomatic S320F, and 1 symptomatic G272V carrier) with 30 cognitively normal controls and 52 patients with Alzheimer disease. Results: [ 18 F]Flortaucipir BPND images showed overall highest binding in the symptomatic carriers. This was most pronounced in the symptomatic R406W carrier in whom tau binding exceeded the normal control range in the anterior cingulate cortex, insula, amygdala, temporal, parietal, and frontal lobe. Elevated medial temporal lobe BPND was observed in a presymptomatic R406W carrier. The single symptomatic carrier and 1 of the 3 presymptomatic P301L carriers showed elevated [ 18 F]flortaucipir BPND in the insula, parietal, and frontal lobe compared to controls. The symptomatic G272V carrier exhibited a widespread elevated cortical BPND, with at neuropathologic examination a combination of 3R pathology and encephalitis. The L315R presymptomatic mutation carrier showed higher frontal BPND compared to controls. The BPND values of the S320F presymptomatic mutation carrier fell within the range of controls. Conclusion: Presymptomatic MAPT mutation carriers already showed subtle elevated tau binding, whereas symptomatic MAPT mutation carriers showed a more marked increase in [ 18 F]flortaucipir BPND . Tau deposition was most pronounced in R406W MAPT (pre)symptomatic mutation carriers, which is associated with both 3R and 4R tau accumulation. Thus, [ 18 F]flortaucipir may serve as an early biomarker for MAPT mutation carriers in mutations that cause 3R/4R tauopathies.